Insignificant small can still be mighty: Trend of chronic kidney disease in Nigeria - Oluwaseyi Abiodun Akpor; Abigael Oluwaseyi Adeoye; Blessing Awhin; Olaolorunpo Olorunfemi (Wolters Kluwer Medknow Publications, 2021)
The global burden of chronic kidney diseases (CKDs) kept increasing, and it is a leading cause of mortality and morbidity rate in most African countries. The burden of CKD is felt more in developing countries where there is no adequate social security system or health insurance to meet the huge financial demands the disease places on its sufferers and their families. It is also noted that this disease affects the economically productive age group unlike in developed countries where the elderly are more affected. The prevalence of CKD was found to be highly related to age, gender, hypertension, obesity, history of diabetes mellitus, use of herbal medicines, and prolonged use of nonsteroidal anti-inflammatory drugs in Nigeria. The majority of CKD cases were not clinically recognized promptly, mainly because of the lack of patients' awareness about CKD and associated risk factors. Therefore, health awareness should be intensified by the nurses on lifestyle modification by individuals at risk of CKD, prompt management, good compliance with prescribed medications, avoidance of self-medication, and indiscriminate use of over-the-counter drugs. In addition to that, nurses also need to advocate for regular population screening, and efforts should be made at all levels of care to reduce the negative impact of the disease and complications on the patients.